5x+6x-64=3x-65

Simple and best practice solution for 5x+6x-64=3x-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6x-64=3x-65 equation:


5x+6x-64=3x-65

We simplify the equation to the form, which is simple to understand
5x+6x-64=3x-65

We move all terms containing x to the left and all other terms to the right.
+5x+6x-3x=-65+64

We simplify left and right side of the equation.
+8x=-1

We divide both sides of the equation by 8 to get x.
x=-0.125

See similar equations:

| 4v-2=10 | | 5x^2=2x+1 | | 6x+19x=25 | | 4x+2+6x-1=13x+1 | | 18-6y=0 | | 4x+3=42 | | 10=3f+1 | | 2b+1=7 | | 4x-5=-1x-30 | | -2x-10+7x=6x+14-4x | | x+14=-32-9 | | -6y+13=-5(y-4) | | 13x=-7-3-20 | | 4x+3x=-35 | | Y+13-7y=-5(y-4) | | 16x+2=-17 | | 22-5x+9x=-2(-6x+5) | | 3y^2+z= | | -33-6y+19=-23y+56+7y | | 7(x+2)=5x+2+6x | | 3x^3-10x^2+50x= | | -2a-9= | | 8(r-2)=r-22+5r | | x*x+x-1=0 | | 9x-4x+3=60 | | x^2+26x+64=0 | | K-14+5k=2(k+3) | | 6y=5x^2-2 | | x-2=x*x-1 | | K-18+5k=2(k+1) | | 2(9x-6)+8(6x-7)=-29 | | 19+6y-1=17y-9-2y |

Equations solver categories